Chemoresistance factors in non-small cell lung cancer - А. I. Shevchenko; А. P. Коlesnik; А. V. Каdzhoian; V. А. Кuzmenko (Zaporozhye State Medical University, 2016)
Lung cancer takes the leading position in cancer morbidity and mortality structure in the world and Ukraine. Advanced stages are diagnosed in more than 70% of lung cancer patients. Chemotherapy remains the main method of treatment for advanced lung cancer. Currently, the standard of chemotherapy in patients with III-IV stages of non-small cell lung cancer (NSCLC) is a combination of cisplatin/carboplatin with paclitaxel, etoposide, gemcitabine and vinorelbine. Although, the objective response rate after chemotherapy treatment is only about 20-50%. Low rates of chemotherapy efficacy are connected with chemoresistance of tumor to definite chemotherapeutic agents. Tumor chemoresistance is the result of different tumor intracellular mechanisms activity. Basing on current data we tried to analyze prognostic and predictive value of main chemoresistance factors in NSCLC. Conclusions. Nowadays we can certainly affirm that chemoresistance to cisplatin in NSCLC is due to increased expression of ERCC1 (Excision repair cross-complementation group 1 protein), BCRP; and resistance to taxanes is connected with elevated expression of β-tubuline III class; and tumoral chemoresistance to gemcitabine is due to high RRM1 (Ribinucleotide reductase M1) expression. High expression of BRCA1 (Breast Cancer 1) protein in tumors leads to increase of tumor cells resistance to cisplatin, but at the same time it increases the sensitivity to taxanes. Therefore, investigation of tumor chemoresistance plays an important role in algorithms' creation for optimal chemotherapy schemes selection in patients with different stages of NSCLC in order to achieve the best tumor response to treatment and improve overall and disease-free survival. The information of main NSCLC chemoresistance factors, its prognostic and predictive value are presented in this overview.